2016
DOI: 10.1016/j.jfoodeng.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Development of rheological and sensory properties of combinations of milk proteins and gelling polysaccharides as potential gelatin replacements in the manufacture of stirred acid milk gels and yogurt

Abstract: Please cite this article as: Pang, Z., Deeth, H., Prakash, S., Bansal, N., Development of rheological and sensory properties of combinations of milk proteins and gelling polysaccharides as potential gelatin replacements in the manufacture of stirred acid milk gels and yogurt, Journal of Food Engineering (2015Engineering ( ), doi: 10.1016Engineering ( /j.jfoodeng.2015 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 40 publications
4
31
0
Order By: Relevance
“…In addition, the confocal microstructure by Pereira, Matia‐Merino, Jones, and Singh () showed the dense and low porosity fat‐protein matrix, which Krzeminski et al () explained as the fat globules occupying the intermicellar spaces. Porous branched protein networks of casein micelle can be seen clearly in skim, pectin, and beta glucan yoghurts which are in agreement with previous observations (Pang, Deeth, Prakash, & Bansal, ; Sanchez, Zuniga‐Lopez, Schmitt, Despond, & Hardy, ). The visible spherical structure of casein micelle had a general diameter of 0.3 μm and the porous structure had a general diameter of 0.5 μm.…”
Section: Resultssupporting
confidence: 92%
“…In addition, the confocal microstructure by Pereira, Matia‐Merino, Jones, and Singh () showed the dense and low porosity fat‐protein matrix, which Krzeminski et al () explained as the fat globules occupying the intermicellar spaces. Porous branched protein networks of casein micelle can be seen clearly in skim, pectin, and beta glucan yoghurts which are in agreement with previous observations (Pang, Deeth, Prakash, & Bansal, ; Sanchez, Zuniga‐Lopez, Schmitt, Despond, & Hardy, ). The visible spherical structure of casein micelle had a general diameter of 0.3 μm and the porous structure had a general diameter of 0.5 μm.…”
Section: Resultssupporting
confidence: 92%
“…Protein solubility will increase if excessive acid treatment is performed, since according to Pang et al (2016)-positive ions in acids that cause proteins (initially neutral or zero) to be positively charged. The further that the acidity of the protein solution is from the isoelectric point, the more soluble it will be.…”
Section: Characterization Of the Initial Productmentioning
confidence: 99%
“…() found that the viscoelasticity of WPI‐cross‐linked waxy maize starch mixed gels increased with an increase in the starch concentration at pH 7.00 in the presence of 100 m m NaCl. WPI and starch mixtures have recently been widely used in food applications (Cheong et al ., ; Pang et al ., ; Salem et al ., ).…”
Section: Introductionmentioning
confidence: 99%